Misidentifications of specific forms of cross-frequency coupling: three warnings - Hyafil, Alexandre (Frontiers in Neuroscience, 2015)
Cross-frequency coupling between neural oscillations has received increased attention over the last decade, as it is believed to underlie a number of cognitive operations in different brain systems. Coupling can take different forms as it associates the phase, frequency and/or amplitude of coupled oscillations. These specific forms of coupling are a signature for the underlying network physiology and probably relate to distinct cognitive functions. Here I discuss three caveats in data analysis that can lead to mistake one specific form of cross-frequency coupling for another: 1, bicoherence assesses the level of phase-amplitude and not of phase-phase coupling as commonly accepted; 2, a test for phase-amplitude coupling can indeed signal phase-frequency coupling when the higher frequency signal is extracted using a too narrow band; 3, An oscillation whose frequency fluctuates may induce spurious amplitude anticorrelations between neighbouring frequency bands. I indicate practical rules to avoid such misidentifications and correctly identify the specific nature of cross-frequency coupled signals.